Probing into the obstacles faced by internship student-teachers in designing lesson plans - Diana Achmad; Endang Komariah; Wahyuni Miftahhul Jannah; Tgk Maya Silviyanti (Studies in English Language and Education, 2023)
This study aims to find out the problems faced by student teachers in an internship program in designing lesson plans at schools. A lesson plan is one of the essential instructional designs that should be considered to achieve a successful teaching and learning process. For teachers, a lesson plan is a guideline that will be used in teaching to achieve learning objectives. This research used a qualitative method. The participants were selected by using purposive sampling. They were seven students of the English Education Department of Universitas Syiah Kuala who were taking an internship program. The data collection was carried out through document analysis and interviews. The results showed that all student teachers strived to design their lesson plans based on the 2013 Curriculum. There were several problems faced by the students, such as (1) formulating the indicators of competency achievement, (2) writing learning objectives, (3) finding suitable materials, (4) selecting learning methods, (5) choosing learning media and resources, (6) formulating activities, and (7) creating an assessment. The results of the interview also revealed the same. Thus, it is recommended that student teachers should receive more training, both theoretically and practically, in designing the lesson plan based on the 2013 Curriculum as required by the Ministry of Education in Indonesia.